Nogai version of the epic “Edige”: review of versions and history of study - Zakirova I.G. (Золотоордынское обозрение)
Purpose of the study: This work is aimed at reviewing and systematizing variants of the Nogai version of the epic “Edige”, introducing unexplored variants into scientific circulation, and compiling a complete list of existing texts. Research materials: Nogai versions of the epic “Edige”. Along with well-known texts, variants published in pre-revolutionary periodicals have been introduced into scientific circulation. The results of the study and its scientific novelty: The present work proves that the Nogai versions of the dastan about Edigei are numerous, but have not yet become the object of a specialized monographic study. Before the revolution, the variants were recorded and published in Russian translation by domestic researchers. The only pre-revolutionary version in the Nogai language was published by M. Osmanov. The scientific novelty of the study lies in the fact that a review of all known options and a comparative analysis of individual episodes and motives was carried out. Variants that have not been studied by Nogai scientists have been identified. The hitherto unexplored version of A.P. Kulebyakin has been introduced into scientific circulation; it can rightfully be called the first consolidated text of the epic. Among other things, the relationship of some texts to the Nogai version is disputed. The Nogai variants differ in the names of the characters and have original motives, yet the originality of the motives is not stemming from a national standpoint but mainly local in nature. The Nogai, Crimean Tatar variants, and the Astrakhan Tatar variants are close to each other in plot.